Flexibility and constraint in the evolution of gene expression and behavior - Fischer, Eva Kristin, author; Hoke, Kim L., advisor; Ghalambor, Cameron K., committee member; Hentges, Shane T., committee member; Mueller, Rachel L., committee member (Colorado State University. Libraries, 2015)
Our understanding of how underlying molecular, neural, and physiological mechanisms contribute to phenotypic evolvability remains limited. Central to understanding the evolutionary potential of phenotypes is an understanding of the extent to which the mechanisms underlying phenotypic differences are flexible versus constrained. My dissertation takes advantage of the unique evolutionary history of Trinidadian guppies (Poecilia reticulata) to explore patterns of flexibility and constraint at three levels. In the first study of my dissertation, I examined genetic and developmental influences on variation and covariation in a suite of behavioral traits to understand whether correlations among traits constrain adaptation to novel environments. I reared guppies from high- and low-predation source populations in environments with and without predators to mimic native and novel environmental conditions and characterized differences in a suite of 21 behaviors measured in four behavioral assays. I found that behavioral variance and covariance structure were altered in novel environments in a manner that likely shaped subsequent selection. My findings suggest that divergence in a novel environment was not constrained by trait correlations in the native environment, and that plastic changes in covariance structure may in fact influence the form of adaptation. In the second study of my dissertation I examined associations between gene expression (transcriptomic) differences and behavior to understand how underlying transcriptional mechanisms mediate behavioral flexibility across developmental and evolutionary timescales. I reared guppies and assayed behavior as before, and quantified whole-brain gene expression from each individual. My dataset allowed me to relate changes in the expression of single genes and gene networks to behavior across genetic backgrounds and rearing environments. I found that conserved gene networks had flexible relationships with behavior, suggesting that alternative transcriptional solutions may give rise to similar behavioral phenotypes across timescales. I propose that this combination of conservation and flexibility balances phenotypic robustness and evolvability in novel environments. Recent studies have considered whether similar phenotypes also share underlying mechanisms, but data are conflicting. In the third study of my dissertation, I compared gene expression signatures associated with adaptation in two distinct evolutionary lineages to ask whether parallel, independent evolutionary events rely on shared mechanisms. I used transcriptomic approaches to quantify genetic and developmental differences in brain gene expression in two high- and low-predation guppy population pairs that represent distinct evolutionary lineages. I found evidence for both shared and distinct transcriptional mechanisms associated with adaptation. Moreover, I demonstrated that expression differences are more likely to evolve in genes that were highly connected to other genes in a gene network. Application of network analyses to transcriptomic data is in its infancy, and an influence of network position on expression divergence has not been previously demonstrated. In summary, I used novel, integrative approaches to study mechanisms of behavioral divergence at multiple levels and found evidence for a combination of conservation and flexibility across levels of biological organization and timescales.
Keywords: flexibility; behavior; transcriptomics; neuroethology; Poecilia reticulata